MOTHERS' PERCEPTION OF TODDLERS ABOUT STUNTING IN THE WORKPLACE OELE HEALTH CENTER, ROTE DISTRICT NDAO - Marzella Artanti Bailaen; Petrus Romeo; Marni Marni (HEARTY, 2026)
Stunting is a chronic nutritional problem that remains a major public health concern in Indonesia. This study focuses on the perceptions of mothers of toddlers regarding the definition, causes, and prevention of stunting. This study aims to determine the perceptions of mothers of toddlers regarding stunting, its causes, and its prevention in the Oele Community Health Center Work Area, Rote Ndao Regency. This research method uses a qualitative design with a phenomenological approach. Informants were selected using purposive sampling. The main informants were mothers of toddlers, key informants were nutrition program holders, and supporting informants were integrated health post (Posyandu) cadres. Data analysis used the Miles and Huberman (1984) model in (Sugiyono, 2010).The results of this study indicate that all mothers of toddlers understand stunting as a condition of shortness of breath due to malnutrition and that stunting is caused by genetic factors. The most frequently cited causes of stunting are inadequate nutritional intake, suboptimal parenting, and environmental hygiene. Preventive measures include exclusive breastfeeding, immunization, nutritious food, and maintaining good hygiene, although economic constraints and misperceptions about heredity remain.In conclusion, mothers of toddlers understand stunting as a condition of short stature due to malnutrition, although some mothers still attribute it to hereditary factors. According to mothers, the main causes of stunting are low nutritional intake, difficulty eating, and suboptimal parenting. Mothers also believe that stunting is caused by hereditary factors. Preventive measures include exclusive breastfeeding, immunization, and nutritious food. The main obstacle to prevention is economic constraints.